Religious Moderation in Education According to the Qur'an and Hadith - Ipan Maulana; Abdul Aziz (Universitas Muhammadiyah Enrekang, 2023)
Moderation is a moderate thing in religion related to understanding and worship, and it is balanced and not too exaggerated. This article aims to find out whether the Qur'an and Al-Hadith as holy books spoken to the Prophet Muhammad (peace be upon him), have a basis or principle that has enormous potential in inviting Muslims to commit violence and terror against religions other than Islam. In this study, researchers use the method of literature review or library research, which is to review a study whose data is sourced from literature related to the object of research. The results showed that the verses of the Qur'an and Al-Hadith do not invite Muslims to commit violence and exaggeration in everything, especially in religious matters. The Qur'an and Al-Hadith teach and offer to understand and practice religion, which should take a middle path. Even balance is a necessity that belongs to the laws of nature.